ANALISIS MOTIVASI BELAJAR FISIKA SISWA DI SMPN 1 KAMPAR KIRI TENGAH SELAMA MASA PANDEMI COVID-19 - Dwi Hariyati; Azhar Azhar; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The existence of learning motivation that comes from the teacher and high learning interest from the students themselves can affect the increase in student achievement. Learning achievement obtained by students is influenced by high learning motivation, because with high learning motivation a student will do something that he is interested in and likes. This study aims to determine and analyze the level of motivation to study physics at SMPN 1 Kampar Kiri Tengah during the covid-19 pandemic. This type of research is descriptive research. The samples taken were 90 students from class VII, VIII, and IX each 1 class at each level. The results of this study reveal that from the overall data recapitulation of 4 (four) indicators regarding the learning motivation of SMPN 1 Kampar Kiri Tengah students during the covid-19 pandemic, it can be concluded that 31.44% have low motivation which has a percentage of 44.11%. . That is, from the indicators mentioned as many as 40 statement items used in this study, it can be seen that student learning motivation is low during the covid-19 pandemic.Keywords: motivation, physics, covid-19.